„Ezek a’ practikák, és módok igen nagyra böcsültetnek…”: Műfajkeveredés Tarnóczi István jezsuita elmélkedésgyűjteményeiben - Kónya, Franciska (Studia Litteraria, 2013)
The seven works of Tarnóczi István (1626–1689) written on Hungarian are prayer- and meditational books. Some recent research on devotional literature is mentioning the passage between the genres in these texts: how the meditation is mixing with other kind of pious texts (prayer, catechism, etc.). This study examines the specific realization of this in the literary work of the Jesuit writer. It represents the changing mode of treatiselike, didactic texts with meditations, prayers. This paper also investigates the role of the presumed reader layer, how it influences the stylistic and rhetorical aspects of these books. The main message is usually transmitted through several chapters as a didactic treatise, which is followed by practical exercises: prayers and meditative texts formulated in first person. The scriptural references, the indications and quotations of religious and secular writers, the thesis-like parts containing expressive and colorful examples contribute to the comprehension, which is a condition for good deeds. The frequently used expression of „practicing the presence of God” is both an intellectual work and a volitional action. On one hand, the prayers formulated in first person deepened the meditation, while on the other hand through these the theological message could reach more easily the pious reader.